Factors associated with the development of dental defects acquired in the extrauterine environment - Judith Rafaelle Oliveira PINHO; Erika Barbara Abreu Fonseca THOMAZ; Cecília Cláudia Costa RIBEIRO; Cláudia Maria Coelho ALVES; Antônio Augusto Moura da SILVA (Sociedade Brasileira de Pesquisa Odontológica, 2019)
Abstract This study aimed to analyze the association of sociodemographic, child health, healthcare service, and access indicators with developmental defects of enamel (DDE) acquired outside the uterus, based on gestational factors. A cohort of births was carried out, and 982 children aged 12 to 30 months were examined. A total of 1,500 women were followed up as of the 5th month of gestation, and the child's gestational age was evaluated at follow-up. The clinical examination was performed as recommended by the World Health Organization, and defects were classified using the modified DDE index. Six models were considered: presence of DDE (Model 1) or opacities (Model 4), number of teeth with DDE (Model 2) or opacities (Model 5), and incidence rate of DDE (Model 3) or opacities (Model 6). Associations were estimated by relative risk (RR) in Poisson regression models. In the adjusted analysis, the mother's lowest education level was associated with the highest occurrence of DDE in Models 1 (RR = 26.43; p = 0.002), 2 (RR = 9.70; p = 0.009), and 3 (RR = 5.63; p = 0.047). Breastfeeding for over 12 months (RR = 0.45; p = 0.030) and recent use of anti-infection drugs (RR = 0.20; p = 0.039) had a protective effect on DDE (Model 1). The factors associated with the highest incidence of opacities were not having health insurance (RR = 2.00; p = 0.043) (Model 5), and belonging to a family of poor social class (RR = 4.67; p = 0.007) (Model 6). Children in a situation of socioeconomic vulnerability have a higher risk of presenting extrauterine DDE. Breastfeeding was a protection factor for DDE development.